Quality of life among patients with chronic liver disease with Hepatorenal syndrome = - Entesar Saied Mohamed; Khairia Abobakr Elsawi; Nagat Elmorsy Ibrahim (Cairo : Entesar Saied Mohamed, 2018)
Background: Hepatorenal syndrome is a unique form of functional renal failure due to diminished renal blood flow. It is a severe complication that affects patients with liver cirrhosis and ascites. Assessing quality of life (QoL) of individuals with chronic diseases has become a common clinical practice The aim of this study was to assess quality of life among liver cirrhosis patients with hepatorenal syndrome. Sample, A convenient sample of 100 adult patients diagnosed with liver cirrhosis admitted to medical wards at one of Cairo university affiliated hospitals was recruited as study sample. Design, A descriptive research design was utilized. Data collection was doneusing two tools including tool 1 demographic and medical related data and tool 11, Quality of life for patients with chronic liver disease .Results. The study revealed that (52%) of patients were above 50 year of age with mean of (51.91±5.36), about(96%) of them were married, most of studied sample about(78%) of patients were employed have monthly income more than 1000 L.E.As regard to medical data about (74%) of patients had prior knowledge regarding chronic liver disease, and the source of knowledge(72%) was doctor. About (55%) of patients have hepatitis C, about (77%)of patients were frequently readmitted complaining of hematemsis , there was decrease in glomerularfiltration rate with increase in creatinne level. Regarding QOL domain about (46% - 39% - 43% and 32% ) of patients were feeling abdominal discomfort, feeling tired, muscles cramp, unable to hold or carry heavy objects respectively, while (51% and 47%) of patients were feeling unhappy and worried about the effect of disease on their family respectively. Finally the total mean score of quality of life among the studied sample equal(96%) indicating moderate quality of life
Thesis (M.Sc.) - Cairo University - Faculty of Nursing - Department of Surgical Nursing
Issued also as CD
Keywords: Hepatorenal syndrome; Liver cirrhosis; Quality of life